Analysis on Significances of SETS-Based Science Teaching Material for PSET Students in Online Learning - Baroroh Iskhamdhanah; Pratiwi Pujiastuti; Setyo Eko Atmojo; Meiwatizal Trihastuti (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This research aims to present the results of the analysis of the significances for SETS-based science teaching materials (Science,Environment, Technology and Society) in online learning which includes (1) the results of significances analysis for SETS-based science teaching materials, (2) the benefits of SETS-based science teaching materials in online learning. This research was conducted at the PGRI Yogyakarta University using qualitative research methods. Data was collected through observation, unstructured interviews and documentation. The results showed that (1) SETS-based science teaching materials is needed by students at PGRI Yogyakarta University in the distance or online learning process in the midst of the Covid-19 pandemic to facilitate the teaching and learning process, (2) the benefits of SETS-based science teaching materials in online learning are that with SETS-based teaching materials students can transform knowledge in the form of technology and develop students' social skills. With the use of SETS-based teaching materials, students are hopefully in ease to access teaching materials because there are no limitations between space and time. In addition, students can explore science knowledge by involving real life and the environment in which they live and can provide benefits to the community. Keywords: Teaching Materials, SETS-Based Science Material, Online Learning